1982
DOI: 10.1007/bf00405890
|View full text |Cite
|
Sign up to set email alerts
|

Do cyanobacteria contain ?mammalian-type? cytochrome oxidase?

Abstract: The cytochrome content of membranes isolated from seven species of cyanobacteria was investigated in terms of conventional difference spectra, carbon monoxide difference spectra, photoaction spectra and photodissociation spectra, and by extraction of acid-labile heme followed by spectral identification. In addition, the effect of various inhibitors and activators on the oxidation of horse heart cytochrome c by the membrane was studied. Both the spectral features and the properties of the cytochrome oxidase rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…Table 2 shows the cyt oxidase activity together with % recoveries of this activity, and of protein, in CM and ICM frac- by 0.1 mM sulfide, 1.0 mM azide, and 20 mM salicyl aldoxime (a potent copper-chelating agent; cf. [22]), and strongly inhibited also by carbon monoxide (table 3). The reaction was sensitive to elevated ionic strength and stimulated by Tween 80.…”
Section: Resultsmentioning
confidence: 95%
“…Table 2 shows the cyt oxidase activity together with % recoveries of this activity, and of protein, in CM and ICM frac- by 0.1 mM sulfide, 1.0 mM azide, and 20 mM salicyl aldoxime (a potent copper-chelating agent; cf. [22]), and strongly inhibited also by carbon monoxide (table 3). The reaction was sensitive to elevated ionic strength and stimulated by Tween 80.…”
Section: Resultsmentioning
confidence: 95%
“…Spectroscopic (6), inhibitor (7), and EPR studies (8), indicated that cyanobacterial respiratory chains contain an aa 3 -type cytochrome c oxidase. Finally, a gene cluster, encoding subunits II, I, and III of the aa 3 -type cytochrome c oxidase has been cloned from Synechocystis PCC 6803 (9).…”
Section: ؊1 Smentioning
confidence: 99%
“…The interaction with different cytochromes and plastocyanin was investigated and both cytochrome c 6 and plastocyanin were proposed as potential electron donors for the cyanobacterial CcO (22). This is interesting because cytochrome c 6 and plastocyanin have the same function in photosynthetic electron transport (Fig. 7) (23) and replace each other depending on the growth conditions (24).…”
Section: ؊1 Smentioning
confidence: 99%
See 1 more Smart Citation
“…The relative ratios of the different electron carriers in heterocyst and vegetative cell membranes are listed in Table I ble) in membranes from both cell types. (24) for vegetative cells from a number of cyanobacterial species.…”
Section: Resultsmentioning
confidence: 99%